Cardiovascular diseases crossroads: cGAS-STING signaling and disease progression - Khan, Muhammad Shehzad; Khan, Shahid Ullah; Khan, Safir Ullah; Suleman, Muhammad; Shan Ahmad, Rafi u; Khan, Munir Ullah; Tayyeb, Jehad Zuhair; Crovella, Sergio; Harlina, Putri Widyanti; Saeed, Sumbul (Current problems in cardiology, 2024)
It is now widely accepted that inflammation is critical in cardiovascular diseases (CVD). Here, studies are being conducted on how cyclic GMP-AMP synthase (cGAS), a component of innate immunity's DNA-sensing machinery, communicates with the STING receptor, which is involved in activating the immune system's antiviral response. Significantly, a growing body of research in recent years highlights the strong activation of the cGAS-STING signalling pathways in several cardiovascular diseases, such as myocardial infarction, heart failure, and myocarditis. This developing collection of research emphasises these pathways' crucial role in initiating and advancing cardiovascular disease. In this extensive narrative, we explore the role of the cGAS-STING pathway in the development of CVD. We elaborate on the basic mechanisms involved in the onset and progression of CVD. This review explores the most recent developments in the recognition and characterization of cGAS-STING pathway. Additionally, it considers the field's future prospects while examining how cGAS-STING pathway might be altered and its clinical applications for cardiovascular diseases.